Archean to Early Paleoproterozoic Tectono-Magmatic Evolution of the Western Rae Craton ... - Neil, Benjamin (University of Alberta Library, 2024)
The Rae craton is one of the largest Archean–Paleoproterozoic age terranes on Earth and preserves >1.6 billion years of the planet’s history. However, significant uncertainty remains regarding how and when the crust of this craton was created and reworked. This thesis investigates the nature and evolution of continental crust in the western Rae craton, with a focus on the Nonacho Lake area (“Nonacho area”) of the Northwest Territories. The techniques used in this study include bedrock mapping, whole-rock geochemical and isotopic analyses, and accessory mineral trace-element and isotopic analyses. Granitoid and orthogneiss rocks (“granitoids”) with zircon U-Pb dates >3.0 Ga and whole-rock Sm-Nd depleted mantle model ages >3.2 Ga are shown to be widely distributed throughout the western Rae craton. They define a large (~1000 x 100 km) basement block referred to herein as the Perry River terrane (PRT). The PRT primarily comprises 3.3–3.1 Ga sodic tonalites and granodiorites that have chondritic to ...